Modification of the electric field distribution in a diffuse streamer-induced discharge under extreme overvoltage. (23rd May 2019) - Brisset, Alexandra; Gazeli, Kristaq; Magne, Lionel; Pasquiers, Stéphane; Jeanney, Pascal; Marode, Emmanuel; Tardiveau, Pierre
Abstract: The present work is devoted to the study of the spatio-temporal distribution of the reduced electric field (REF) in a 10 ns diffuse atmospheric air discharge at very high overvoltage, in a pin-to-plane electrode geometry. The REF is derived through the intensity ratio of two well-known transitions of molecular nitrogen: N2 (C–B, v ′ = 2, v ″ = 5) and N2 + (B–X, v ′ = 0, v ″ = 0). The achieved temporal resolution is 500 ps, while the spatial resolution is better than 300 μ m and 400 μ m in the axial and radial direction, respectively. Due to the fast rise time of the voltage pulse, the total electric field is dramatically disturbed by the contribution of the Laplacian field, contrary to low-voltage streamer discharges. Electric field values above the ionization threshold are sustained all along the plasma channel. The dynamics of the high-voltage diffuse discharge seem similar to those of classical streamers with a very high field zone propagating towards the plane electrode then followed by a backward neutralization wave. However, some noticeable discrepancies are reported between the experimentally-obtained distributions of the axial electric field at 65 and 85 kV and those computed by means of a fluid model. They stress in particular the origin and the role of the background electrons in the discharge dynamics. Several limitations of the applicability of the intensity-ratio method for the study of very transient phenomena are also discussed. At first, the effect of the temporal integration of the signals is addressed by comparing them with an artificial averaging of the modeling results. Then, the effect of the non-stationarity of the collected signals is put forward by applying the intensity-ratio method under steady-state assumption or not. Lastly, the overestimation of the electric field in the discharge front due the relatively long effective lifetime of N2 (C, v ′ = 2) compared to the discharge dynamics is discussed.